me ajudem por favor
Anexos:
![](https://pt-static.z-dn.net/files/d6f/ebe6bcec48a89fcdc45e230c54f248b0.jpg)
Soluções para a tarefa
Respondido por
0
é só substituir:
x=-(-7) +√(-7)² - 4 x 1 x 10 ÷ 2
x= 7 + √49 - 40 ÷ 2
x= 7 + √9 ÷ 2
x= 7 +/- 3 ÷ 2
x= 10/2 = 5
ou x= 4/2 = 2
ESPERO TER AJUDADO!
x=-(-7) +√(-7)² - 4 x 1 x 10 ÷ 2
x= 7 + √49 - 40 ÷ 2
x= 7 + √9 ÷ 2
x= 7 +/- 3 ÷ 2
x= 10/2 = 5
ou x= 4/2 = 2
ESPERO TER AJUDADO!
Perguntas interessantes
Química,
11 meses atrás
Geografia,
11 meses atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Física,
1 ano atrás
Matemática,
1 ano atrás
Português,
1 ano atrás